Development of cross-border e-commerce in China and its capabilities in the implementation of the project «One belt – one way» - Wang, Yuan (Journal of the Belarusian State University. Economics, 2020)
The implementation of China’s «One Belt – One Road» policy has brought unprecedented opportunities for the development of cross-border e-commerce. But at the same time, there are many problems in the development process: scarcity of qualified specialists, lag of logistics development, payment risk. Possible challenges in the cross-border e-commerce in China within give project are analyzed. Corresponding countermeasures are proposed.